1997
DOI: 10.1002/(sici)1098-2736(199711)34:9<949::aid-tea7>3.0.co;2-u
|View full text |Cite
|
Sign up to set email alerts
|

Multimedia and understanding: Expert and novice responses to different representations of chemical phenomena

Abstract: In two experiments, we examined how professional chemists (i.e., experts) and undergraduate chemistry students (i.e., novices) respond to a variety of chemistry representations (video segments, graphs, animations, and equations). In the first experiment, we provided subjects with a range of representations and asked them to group them together in any way that made sense to them. Both experts and novices created chemically meaningful groupings. Novices formed smaller groupings and more often used same-media rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
301
0
32

Year Published

1999
1999
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 577 publications
(340 citation statements)
references
References 26 publications
7
301
0
32
Order By: Relevance
“…Studies indicate that students' RC is closely related to students' conceptual understanding of the domain (Kozma & Russell, 1997;Stieff, 2011). However, these studies did not seek to empirically distinguish between content knowledge in the domain (CK) and RC.…”
Section: Representational Competence (Rc)mentioning
confidence: 99%
See 3 more Smart Citations
“…Studies indicate that students' RC is closely related to students' conceptual understanding of the domain (Kozma & Russell, 1997;Stieff, 2011). However, these studies did not seek to empirically distinguish between content knowledge in the domain (CK) and RC.…”
Section: Representational Competence (Rc)mentioning
confidence: 99%
“…First, we examine students' RC and CK on photosynthesis as well as the relationship between these two constructs. Previous research indicated that students' RC is closely related to students' conceptual understanding of the domain, but these studies did not empirically distinguish between CK and RC (Kozma & Russell, 1997;Stieff, 2011). We would like to answer the following research questions: (1) What role does students' CK play in relation to students' RC and vice versa?…”
Section: Current Studymentioning
confidence: 99%
See 2 more Smart Citations
“…Ahora, el aprendizaje asistido por la visualización científica molecular está cambiando la manera en que los estudiantes conciben la química. 9 En un proyecto de investigación cooperativa financiado por la Fundación de la Ciencia Nacional de los Estados Unidos, sobre la visualización molecular en la enseñanza de la química, se encontró que de todos los modelos moleculares considerados, incluyendo los modelos físicos, las herramientas de visualización computacional fueron los que marcaron la diferencia en la manera en que los alumnos asimilan el conocimiento. [10][11][12][13][14][15] La visualización científica molecular se ha utilizado como una herramienta valiosa en el aprendizaje de la química en el salón de clases.…”
Section: Introductionunclassified